If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5/6x-7=1/x-1
We move all terms to the left:
5/6x-7-(1/x-1)=0
Domain of the equation: 6x!=0
x!=0/6
x!=0
x∈R
Domain of the equation: x-1)!=0We get rid of parentheses
x∈R
5/6x-1/x+1-7=0
We calculate fractions
5x/6x^2+(-6x)/6x^2+1-7=0
We add all the numbers together, and all the variables
5x/6x^2+(-6x)/6x^2-6=0
We multiply all the terms by the denominator
5x+(-6x)-6*6x^2=0
Wy multiply elements
-36x^2+5x+(-6x)=0
We get rid of parentheses
-36x^2+5x-6x=0
We add all the numbers together, and all the variables
-36x^2-1x=0
a = -36; b = -1; c = 0;
Δ = b2-4ac
Δ = -12-4·(-36)·0
Δ = 1
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{1}=1$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-1)-1}{2*-36}=\frac{0}{-72} =0 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-1)+1}{2*-36}=\frac{2}{-72} =-1/36 $
| 18=~6k | | 7c–5=30 | | 6(a+3)=18+6а | | (X+2)(x-3)=(x-3)^2 | | 2/3+x/2=3/8 | | 7(x+3)+5=7x+4 | | 3(x+2)=-5-2(×-3 | | 20-3x=12-5x | | 4(x-4)+3x=10+5x | | 4y-6=2y;3 | | 2(3b×b)=864 | | 2p×3p×=10p | | .4(x-4)+0.5=1-0.2(8-2x)-0.5 | | -2.2-0.1c=-1.9 | | 9/x+7=3/8 | | x+1/2=180 | | 3(x-7)=13+10x | | 3(x+-2)=5x+8 | | 5t2-4t=2 | | 0.83x=12.5 | | 3=60x | | 40x-20=6x+180 | | 1*m+2*m=45 | | 0.25k-7.75=2 | | x^2=-3x+4* | | w/1/5-4=w+4/3 | | 3x=2/3+(3x-2) | | 3x=(2/3)+(3x-2) | | x^2-16=0* | | 3(3x-1)=2(2x+3) | | 7x+2=6(x-2)-7 | | 3x+2=10−3x |